CHARACTERISTICS OF PSYCHOLOGICAL PROTECTION SKILLS TO GAME ADDICTION AMONG ADOLESCENTS - Lueang-on, Kantharat; Choochom, Oraphin; Prayai, Narumol (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to study the characteristics of psychological protection skills to game addiction among adolescents. The researcher study quantitative information using in - depth interviews and questionnaires with 15 keys informants selected through purposive sampling. The data were collected from five psychiatrists and psychologists, who have more than 5 years of experience in treating and protecting game addiction behaviors or publish at least 3 related academic articles, five adolescents who have high psychological protection skills toward game addiction behaviors with Game - P score ≥ 65 and Game Addiction Screening Test - score 24, and five adolescents who have low psychological protection skills toward game addiction behaviors with Game - P score ≤ 64 and Game Addiction Screening Test - score ≥ 33. The interview uses psychological protection skills to game addiction as a framework before leading to content analysis.The research findings indicate that there are four components of the psychological protection skills to game addiction in adolescents which are self - esteem, self - control, coping strategies, and the understanding of game addiction impact. Participants such as teachers, psychiatrists, psychologists, and academicians can utilize this research to treat and protect game addiction behaviors among adolescents and related groups.